Thermophysical properties of pink guava juice at 9 and 11°Brix - Zainal, B.S.; Abdul Rahman, R.; Ariff, A.B.; Saari, B.N.; Asbi, B.A. (Wiley, 2001)
The effect of temperature on the conservation of pseudoplastic characteristics and on the physical properties of pink guava juice (Psidium guajava L.) variety Beaumont: B-30 with two different total soluble solids (9°Brix and 11 °Brix) was investigated. It was found that the juice exhibits pseudoplastic behavior in the range of shear rate between 40 to 160 s-1 and within pasteurization temperature of 60-90C. While the flow behavior index (n) and density (p) increased, consistency coefficient (K), thermal conductivity (k) and specific heat capacity (Cp) decreased with increasing temperature. The linear regression equations or models for flow behavior index, consistency coefficient, density, thermal conductivity and specific heat capacity were determined with correlation coefficients ranging from 0.75 to 1.00.